THE SHADOW OF VILLAGE COMPANIONS: A PORTRAIT OF VILLAGES' LACK OF INDEPENDENCE IN FINANCIAL MANAGEMENT - Faisol Faisol; Moh Syarif (Jurnal Riset Terapan Akuntansi, 2026)
Village financial management is crucial for creating an independent, transparent, and accountable village government, while simultaneously encouraging more effective development and improving community welfare. This study aims to uncover the village government's dependence on village facilitators in financial management. The method used was a qualitative descriptive case study approach, with data collection through interviews, observation, and documentation. The results show that the entire process of preparing the Village Budget (APBDes) and Village Funds is entirely delegated to village facilitators, while the village secretary and other officials are less actively involved. In fact, the role of village facilitators goes beyond their duties as they participate in financial management and receive compensation from the disbursed Village Funds. This situation is inconsistent with applicable regulations, such as Home Affairs Ministerial Regulation Number 113 of 2014 concerning Village Financial Management and Law Number 6 of 2014 concerning Villages, which emphasize the importance of village independence and accountability. In general, this phenomenon indicates that the independence and accountability of village governments are still weak, and the role of village facilitators has not been optimally implemented as facilitators. Therefore, efforts are needed to increase the capacity of village officials through training and coaching so that they are able to manage village finances independently, transparently, and in accordance with regulations. Keywords: : Village Budget, Village Finance, Village Funds, Village Government, Village Assistants.